PRAKTIK TATAMBA BANYU OLEH GURU SYAIROZI DI KABUPATEN BANJAR (SEBUAH ANALISIS SUFISTIK) - Hamlan Hamlan; Asmaran As; Suriyadi Suriyadi (Jurnal Ilmiah Ilmu Ushuluddin, 2021)
The practice of batatamba is one of the cultural heritages of urang Banjar in South Kalimantan which they still done by some local people to get healthy, both physically and spiritually. This is because since ancient times, physical and spiritual health is something very valuable and very expensive because it has immeasurable value for the perfection of one's life and life. For example, in Antasan Senor Village, Martapura, Banjar Regency there is Tuan Guru Syairozi. To Guru Syairozi, every day many people line up asking for help for various diseases, especially chronic diseases that are difficult to cure, or diseases that are considered as the actions of others, a type of witchcraft. The focus of this research is to determine the batatamba banyu procession by Guru Syairozi and the sufistic dimension of the batatamba banyu practice. The object of his research was the house of Guru Syairozi, Antasan Senor Village, Banjar Regency, Martapura, South Kalimantan Province, using interviews, observation and documentaries. The finding of this research is that the batatamba banyu practice was originally practiced by Guru Syairozi's father himself (KH. Marhasani). Then in 1998, his father passed away to the grace of Allah (died). After forty days after the death of his father, the batatamba banyu practice was continued by him. Until now, Guru Syairozi has been practicing this batatamba banyu practice for about twenty-three years. Healing Guru Syairozi uses the Sufi healing method which views al-maqâmât in Sufism as a basic concept for healing various diseases, especially mental and can also be used as a source of healing for physical ailments. The concept of al-maqâmât which he used to advise the people being treated were repentance, patience, tawakkal, qana'ah, wara ', zuhud and pleasure.